Health Utility of Drinkers' Family Members: A Secondary Analysis of a US Population Data Set. Issue 2 (September 2022) - Thornburg, Benjamin; Bray, Jeremy W.; Wittenberg, Eve
Background. Problematic alcohol use is known to harm individuals surrounding the drinker. This study described the health utility of people who reported having a family member(s) whom they perceived as a "problem drinker."Methods. We conducted a secondary analysis of the US National Epidemiologic Survey of Alcohol and Related Conditions Wave 3 (NESARC-III, 2012–13) data to estimate the independent associations of a family member's problem drinking on the respondent's health utility, also known as health-related quality of life, assessed via the SF-6D. Participants included 29, 159 noninstitutionalized adults, of whom 21, 808 reported perceiving a family member or members as having a drinking problem at any point in that person's life. Respondent drinking was assessed via self-report and diagnostic interview. We used population-weighted multivariate regression to estimate disutility.Results. After adjusting for the respondent's own alcohol consumption, alcohol use disorder (AUD), family structure, and sociodemographic characteristics, the mean decrement in SF-6D score associated with perceiving a family member as a problem drinker ranged from 0.033 ( P < 0.001) for a spouse/partner to 0.023 ( P < 0.001) for a grandparent, sibling, aunt, or uncle. The mean decrement in SF-6D score from having AUD oneself was 0.039 ( P < 0.001).Conclusions. Perceived problem drinking within one's family is associated with statistically significant losses in health utility, the magnitude of which is dependent on relationship type. The adverse consequences associated with problem drinking in the family may rival having AUD oneself.Implications. Family-oriented approaches to AUD interventions may confer outsize benefits, especially if focused on the spouse or partner. Economic evaluation of alcohol misuse could be made more accurate through the inclusion of family spillover effects. Highlights: Spillover effects from problem drinking in the family vary by relationship type. One's perception of their spouse or child as having a drinking problem is associated with a utility decrement of equal magnitude to having alcohol use disorder oneself. Medical decision makers should consider the outsize effects of family spillovers in treatment decisions in the context of alcohol consumption, particularly among spouses and children of problem drinkers. Economic evaluation should consider how to incorporate family spillover effects from problem drinking in alcohol-related models.